The Relationship between Entrepreneurial Culture and Sustainable Competitive Advantage in the Banking Sector - Atiku, Sulaiman Olusegun; Fields, Ziska (Journal of Economics and Behavioral Studies, 2016)
Business sustainability of services-rendering organisations is one of the major concerns for those at managerial levels world-wide. This paper offers explanations on how best to achieve sustainable competitive advantage by communicating entrepreneurial values through human resource development programmes in the banking industry. The research reported in this paper adopted a non-experimental research design of ex post facto type, utilising a correlational approach with advanced explanatory design. Based on the principle of convenience sampling, 380 questionnaires were distributed to employees of two Nigerian banks. Three hypotheses were formulated and tested using inferential statistics via two statistical software packages: the IBM Statistical Package for Social Science (SPSS) version 23 and the IBM SPSS Analysis of Moment Structure (AMOS) version 23. The results show that human resource development partially mediates the relationship between entrepreneurial culture and sustainable competitive advantage in the Nigerian banking sector. The results suggest an enhancement of entrepreneurial values through continuous learning and development programmes toward sustainable competitive advantage. It is recommended that sustainability of banks operating in Nigeria could be enhanced by communicating and managing entrepreneurial orientations through effective learning and development programmes. Ambidextrous banks will require creativity, innovation and proactive capabilities in the process of exploiting and exploring both current and future business opportunities for sustained competitive advantage.